Quality of Student Administration Services at SMK Negeri 8 Makassar - Akib, Haedar; Anary, Sherina; Sakawati, Herlina (Universitas Negeri Makassar, 2023)
Student satisfaction is an important component of a formal service assessment plan. Thus, schools are required to always improve the quality of all components in the school. This study aims to determine the quality of student administration services and the factors that support and hinder student administration services at SMK Negeri 8 Makassar. The type of research used is descriptive qualitative. The informants in this study were the Head of Administration, Administration Staff, Teachers, Student Council Chairman, and Students. Data collection techniques are carried out through observation, interviews, and documentation. The data analysis techniques used in this study are data collection, data condensation, data presentation, and conclusions. The results showed that student administration services at SMK Negeri 8 Makassar were in the